Filler compound and use of filler compound

By using filler compound with high content of glassy material particles in the filler compound, the problem of cracking of the filler compound during solidification is solved, low shrinkage properties and improved appearance quality are achieved, and construction time and cost are reduced.

CN119504216APending Publication Date: 2025-02-25SAINT GOBAIN PLACO SAS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527742.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-07-21
Filing Date
2021-05-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing filler compounds are prone to cracking during solidification, resulting in poor filler appearance and time-consuming application of gypsum finishes, increasing the time and cost of structural construction.

Method used

A filler compound is developed that contains particles of at least one glassy material, such as expanded perlite, obsidian, etc., which accounts for at least 10% of the dry mass of the filler compound and at least 30% of the diameter of the filler particles is between 50 and 100 microns to reduce shrinkage.

Benefits of technology

The filler compound exhibits low shrinkage properties, with a shrinkage depth of no more than 0.5mm, improving the appearance quality of the filler, reducing the number and time of application of the gypsum finish layer, and reducing the construction cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504216A_ABST
    Figure CN119504216A_ABST
Patent Text Reader

Abstract

The present invention relates to a filler compound and to the use of the filler compound in the assembly of structures. According to the invention, there is provided a filler compound comprising filler particles and a binder wherein the filler particles comprise particles of at least one glassy material and the particles of glassy material are at least 10% by weight of the dry mass of the filler compound, and wherein the binder is at least 10% by weight of the dry mass of the filler compound. At least 30% by weight of the filler particles have a diameter of between 50 and 100 microns (inclusive). The use of the filler compound in the assembly of structures is also described.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with application number 202180047758.9, application date May 25, 2021, and invention name “Filler compounds and uses of filler compounds”. Technical Field

[0002] The present invention relates to a filler compound. The present invention also relates to the use of the filler compound in the erection of a structure. Background of the Invention

[0003] Gypsum wallboard (also known as gypsum board) is commonly used during the construction of structures such as partition walls and / or ceilings. Walls made of gypsum board are conventionally constructed by fixing gypsum board panels to studs or joists. Although experienced builders can minimize the gaps between adjacent gypsum boards, it is impossible to eliminate the gaps between gypsum boards, especially in areas where prefabricated panels need to be cut or trimmed. In addition to gypsum board, structures can also be constructed using other building boards, such as, but not limited to, cement board, concrete board, non-gypsum-based boards, and fiberboard.

[0004] Filler or joint compounds can be used to fill gaps between adjacent building panels. In addition, fillers can also be used to repair damaged areas of building panels, as well as to fill holes, recesses or voids to ensure a smooth finish. When a filler compound is used, the filler compound is inserted into the gap between adjacent building panels, or into the damaged area, or into the hole, recess or void to improve the continuity of the surface. Various forms of filler compounds are known. One type of filler compound is a dry powder that is mixed with water to form a paste before being inserted into the gap between adjacent building panels. A second type of filler compound is provided to the user in the form of a premixed paste. In either case, the filler compound must be allowed to set and dry in the gap between adjacent building panels, or in the damaged area, or in the hole, recess or void before further operations can be performed to improve the aesthetics of the filler.

[0005] The appearance of the filler may be unacceptable due to cracking of the filler compound during the setting process. This cracking occurs when water and / or other fluids evaporate from the filler compound as it dries and sets, which causes the filler compound to shrink. Therefore, to improve the appearance of the filler, a gypsum finishing layer may be used to smooth the surface of the structure.

[0006] The application of finishing layers of gypsum is a time-consuming process. In cases where cracking of the filler compound is severe, typically where the gaps between adjacent building panels are large, several layers of finishing plaster may be required to achieve an acceptable finish. In such cases, each layer of finishing plaster must be allowed to dry before the subsequent layer is added, significantly increasing the length of time it takes to construct a given structure. Furthermore, plasterers are skilled workers, and therefore, applying several layers of finishing plaster can be a significant expense.

[0007] Objects and aspects of the present invention seek to address at least some of these points. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 The measurement of shrinkage depth of filled compounds is demonstrated. Summary of the invention

[0008] According to a first aspect of the present invention, a filler compound is provided, comprising filler particles and a binder, wherein the filler particles comprise particles of at least one glassy material, and further, wherein the particles of the glassy material are at least 10 wt. % of the dry mass of the filler compound, and finally, wherein at least 30 wt. % of the filler particles have a diameter between 50 and 100 microns (inclusive).

[0009] In this way, a filler compound having low shrinkage properties can be provided. A low shrinkage filler compound can be considered as Figure 1 Filler compounds which exhibit a shrinkage depth of at most 0.5 mm when measured as described in Table 2.

[0010] Preferably, the filler compound is a paste. Alternatively, the filler compound is a powder. When the filler compound is a powder, it can be mixed with water or other suitable fluids before use. Therefore, the powder can be hydratable. Preferably, the powder further comprises stucco (CaSO4(1 / 2)H2O). Preferably, the powder comprises calcium sulfate anhydrite (CaSO4). Preferably, the powder comprises stucco and calcium sulfate anhydrite.

[0011] Preferably, the filler compound is a joint filler compound. Joint filler compounds are those compounds used to fill gaps between building panels during assembly of a structure. Features described herein in relation to filler compounds may also be features of joint filler compounds. Furthermore, any of the described advantages of these properties associated with filler compounds may also be relevant when a joint filler compound is provided.

[0012] Preferably, the at least one glassy material comprises expanded perlite, obsidian, pitchstone, pumice, plagioclase, tachylite, scoria, hyalocalstite, sideromelane, microspheres and / or hollow coal particles. Preferably, the glassy material is composed of one of expanded perlite, obsidian, pitchstone, pumice, plagioclase, tachylite, scoria, hyalocalstite, sideromelane, microspheres and / or hollow coal particles. Glassy materials include glassy igneous rocks and siliceous volcanic glasses. Glassy microspheres include those comprising borosilicate glass.

[0013] Microspheres are small spherical particles. Hollow coal particles are lightweight, inert hollow spheres. Preferably, the hollow coal particles contain silica and alumina.

[0014] Preferably, at least 30% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive). More preferably, at least 40% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive). Still more preferably, at least 45% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive).

[0015] Preferably, at most 80% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive). More preferably, at most 75% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive). Still more preferably, at most 60% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive). Still more preferably, at most 55% by weight of the filler particles have a diameter between 63 and 100 microns (inclusive).

[0016] Preferably, at least 35% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive). More preferably, at least 40% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive). More preferably, at least 45% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive).

[0017] Preferably, at most 80% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive). More preferably, at most 75% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive). Still more preferably, at most 60% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive). Still more preferably, at most 55% by weight of the filler particles have a diameter between 50 and 100 microns (inclusive).

[0018] Preferably, the particles of glassy material are at least 15% by weight of the dry mass of the filler compound. More preferably, the particles of glassy material are at least 20% by weight of the dry mass of the filler compound. Still more preferably, the particles of glassy material are at least 20% by weight of the dry mass of the filler compound.

[0019] Preferably, the particles of the at least one glassy material comprise pumice particles. Typically, pumice comprises primarily silicon dioxide and aluminum oxide and trace amounts of other oxides. Still more preferably, the particles of the at least one glassy material consist of pumice particles.

[0020] Preferably, the pumice particles are at least 10% by weight of the dry mass of the filler compound. More preferably, the pumice particles are at least 15% by weight of the dry mass of the filler compound. Still more preferably, the pumice particles are at least 20% by weight of the dry mass of the filler compound.

[0021] Preferably, at least 95% by weight of the filler particles have a diameter below 200 microns. More preferably, at least 95% by weight of the filler particles have a diameter below 125 microns. This feature is advantageous because it improves the surface finish and smoothness of the filled compound.

[0022] Preferably, the adhesive comprises a plaster adhesive. More preferably, the plaster adhesive can be present in an amount between 50% by weight and 30% by weight of the filler compound dry mass. Still more preferably, the plaster adhesive can be present in an amount between 35% by weight and 45% by weight of the filler compound dry mass. Most preferably, the plaster adhesive can be present in an amount of 40% by weight of the filler compound dry mass. Preferably, the adhesive may comprise a polymer adhesive. The adhesive may comprise a plaster adhesive and a polymer adhesive. Preferably, the polymer adhesive is present in an amount of 1.0% by weight to 6.0% by weight of the filler compound dry mass. More preferably, the polymer adhesive is present in an amount of 1.5% by weight of the filler compound dry mass.

[0023] Preferably, 20% to 80% by weight (inclusive) of the filler has a bulk density between 200 and 2000 g / l. More preferably, 20% to 80% by weight (inclusive) of the filler has a bulk density between 200 and 1000 g / l.

[0024] Preferably, the particles of the at least one glassy material include expanded perlite particles. Perlite is an amorphous volcanic glass having the following typical chemical composition (all in weight percentages):

[0025] 70% to 75% silicon dioxide,

[0026] 12% to 15% alumina,

[0027] 3% to 4% sodium oxide,

[0028] 3% to 5% potassium oxide,

[0029] 0.5% to 2% iron oxide,

[0030] 0.2% to 0.7% magnesium oxide,

[0031] 0.5% to 1.5% calcium oxide.

[0032] Expanded perlite is typically formed by heating perlite. Perlite is unusual in that when it is heated, it can expand to up to 20 times its original volume, producing a low density material.

[0033] Preferably, the expanded perlite particles are at least 10% by weight of the dry mass of the filler compound. More preferably, the expanded perlite particles are at least 15% by weight of the dry mass of the filler compound. Still more preferably, the expanded perlite particles are at least 20% by weight of the dry mass of the filler compound.

[0034] Preferably, the filler particles further comprise calcium carbonate particles. Preferably, calcium carbonate particles are at least 5 wt % of the dry mass of the filler compound. More preferably, calcium carbonate particles are at least 10 wt % of the dry mass of the filler compound. Still more preferably, calcium carbonate particles are at least 20 wt % of the dry mass of the filler compound.

[0035] Preferably, the filler compound further comprises a thickener. More preferably, the thickener comprises at least one of starch ether, polyacrylamide, clay, hectorite, bentonite, palygorskite, xanthan gum and / or polyurethane.

[0036] Preferably, the filler compound further comprises a retarder. Preferably, the retarder comprises an organic acid. Preferably, the retarder is present in an amount of 0.02 wt % of the dry mass of the filler compound.

[0037] Preferably, the filler compound comprises an adhesive. Preferably, the adhesive comprises a vinyl acetate polymer and / or a styrene polymer. Preferably, the filler compound further comprises at least one of a microbicide, a fungicide and an antibacterial agent.

[0038] Preferably, the filler compound comprises a cellulose ether. More preferably, the cellulose ether is present in an amount of 0.35 wt % of the dry mass of the filler compound. Preferably, the filler compound comprises a starch ether. More preferably, the starch ether is present in an amount of 0.02 wt % of the dry mass of the filler compound.

[0039] According to a second aspect of the present invention, there is provided the use of the aforementioned filler compound in the assembly of a structure. Preferably, the structure comprises a partition wall or a ceiling. Preferably, the structure comprises a gypsum board, a cement board, a concrete board, a non-gypsum-based board and / or a fiberboard. Preferably, the assembly of the structure comprises a dry lining process. DETAILED DESCRIPTION

[0040] In search of improved filler compounds, different filler compounds with various compositions were prepared.

[0041] Each filler compound was prepared in dry powder form. The prepared filler compounds are described in Table 1 below.

[0042]

[0043]

[0044] To investigate the shrinkage properties of each prepared filler compound, 12.5 mm thick gypsum boards 1, 2 were installed with a gap of 5 mm between them. The gap between the gypsum boards 3 was then filled with the prepared filler compound and the filler compound was allowed to dry for 24 hours. After drying, the filler between the gypsum boards was measured using a caliper to measure the shrinkage depth (X) of the filler compound within the filler, as Figure 1 The measured shrinkage depth for each filler compound was then classified on a scale of 0 to 3 as summarized in Table 2 below.

[0045]

[0046] The analysis conducted on each of the filler compounds prepared produced the following results shown in Table 3.

[0047]

[0048] Examples 1 to 5 show improved performance compared to the comparative examples, wherein the improved performance is the observed reduction in shrinkage. Example 1 shows a shrinkage of less than 0.1 mm, and Examples 1 to 5 all show a shrinkage of 0.5 mm or less. In contrast, Comparative Examples 1 to 8 all show a shrinkage of greater than 0.5 mm. Shrinkage values ​​greater than 0.5 mm are generally undesirable because such shrinkage values ​​can result in poor aesthetics of the filler.

[0049] Further experiments were conducted to investigate the amount of particles of glassy material required to ensure that the filler compound had the desired low shrinkage properties. The filler compound compositions used in these experiments are detailed below.

[0050] Table 4 - Plaster-based powder compounds

[0051]

[0052]

[0053] Table 5 - Polymer-based powder compounds

[0054]

[0055] Table 6 - Polymer-based paste compounds

[0056]

[0057]

[0058] In each case, the weight percentages are measured on the dry mass of the filler compound.In addition, the weight percentage of filler particles having a diameter between 50 and 100 microns (inclusive) is measured using a wetsieving method well known to those skilled in the art.

[0059] Again, the contraction depth was measured as previously described for Figure 1 The determinations were made as described and categorized as summarized in Table 2. The results of Examples 6 to 17 are contained in Table 7 below, each result being the average of five individual experiments and rounded to one decimal place.

[0060] Table 7 - Shrinkage values

[0061]

[0062]

[0063] As can be seen from Table 7, each of Examples 6 to 17 produced a shrinkage value of 1. Therefore, Examples 6 to 17 all showed a measured shrinkage depth of 0.5 mm or less. As previously mentioned, a measured shrinkage depth of 0.5 mm or less is desirable.

[0064] The experimental data provided in connection with Examples 1 to 17 illustrate a number of features. First, it supports that particles of many different glassy materials can produce the desired low shrinkage effect and that the effect is not limited to a single material. Successful results have been demonstrated using hollow coal particles, microspheres, pumice and expanded perlite.

[0065] Furthermore, the experimental data demonstrates that the inclusion of calcium carbonate within the filler compound does not negatively impact its low shrinkage properties. Calcium carbonate has been successfully included in low shrinkage filler compounds without causing any significant reduction in efficacy.

[0066] In addition, the experimental data has shown that successful results are obtained by using various weight percent values ​​of filler particles having a diameter between 50 and 100 microns (inclusive). Finally, the experimental data also shows that a range of weight percents of particles of glassy material can be used to obtain the desired low shrinkage filler compound.

[0067] Finally, experiments were also conducted to illustrate the performance of the exemplary filler compounds previously presented and described versus prior art filler compounds. The filler compounds used in these experiments are detailed in Table 8 below.

[0068] Table 8 - Comparison with existing products

[0069]

[0070]

[0071] In order to measure the shrinkage percentage, a gypsum board substrate is provided, and a circular mold of 3mm depth and 50mm diameter is placed on the surface of the gypsum board. Subsequently, each mold is filled with a filler compound, and the filler compound is flattened so that it completely fills the mold with a flat top surface. Therefore, each filler compound forms a cylinder with a height of 3mm and a diameter of 50mm. Each filler compound is then dried and solidified for 24 hours, and then the height difference between the upper surface of the solidified filler compound and the top of the mold is measured using a laser. The volume change of the filler compound before and after solidification is then calculated, and the volume change is expressed as a shrinkage percentage, as is well known to those skilled in the art. This measurement method is well known in the art and has a standard deviation of ± 1%.

[0072] As can be seen from Table 8, the filler compositions within the scope of the present invention all have much lower shrinkage values ​​than the prior art compositions (the filler compositions within the scope of the present invention are measured against the prior art compositions). This reduction in shrinkage values ​​applies to compounds where plaster is the binder and compounds using a polyvinyl acetate binder. Compounds using a plaster binder show the least shrinkage overall, but each binder according to the present invention shows better shrinkage performance than any of the prior art products.

Claims

1. Filler compound, The filler compound comprises filler particles and a binder, in, The filler particles comprise particles of at least one glassy material, wherein the particles of the glassy material are at least 10% by weight of the dry mass of the filler compound, and wherein at least 30% by weight of the filler particles have a diameter between 50 and 100 microns, inclusive.

2. The filler compound according to claim 1, wherein The particles of the at least one glassy material comprise particles of pumice.

3. The filler compound according to claim 2, wherein: The pumice particles are at least 10 wt % of the dry mass of the filler compound.

4. The filler compound according to claim 3, wherein The pumice particles are at least 20 wt % of the dry mass of the filler compound.

5. A filler compound as claimed in any one of the preceding claims, wherein At least 95% by weight of the filler particles have a diameter below 200 microns, preferably below 125 microns.

6. A filler compound as claimed in any one of the preceding claims, wherein The binder comprises a plaster binder.

7. A filler compound as claimed in any one of the preceding claims, wherein The binder comprises a polymer binder.

8. A filler compound as claimed in any one of the preceding claims, wherein 20% to 80% by weight inclusive of the filler have a bulk density between 200 and 2000 g / l.

9. A filler compound as claimed in any one of the preceding claims, wherein The particles of at least one glassy material comprise expanded perlite particles.

10. The filler compound of claim 9, wherein: The expanded perlite particles are at least 10% by weight of the dry mass of the filler compound.

11. A filler compound as claimed in any one of the preceding claims, wherein The filler particles also include calcium carbonate particles.

12. The filler compound of claim 11, wherein The calcium carbonate particles are at least 5 wt % of the dry mass of the filler compound.

13. A filler compound as claimed in any one of the preceding claims, wherein The filler compound further comprises a thickener.

14. A filler compound as claimed in any one of the preceding claims, wherein The filler compound also includes a retarder.

15. Use of a filler compound as claimed in any one of the preceding claims in the assembly of structures.